A chegada do inbound marketing ao mercado brasileiro - Braulio, Diogo Ferreira de Almeida (2019)
This research has as its theme the arrival of inbound marketing to the Brazilian, analyzing the behavior of the communication market in the country, which loses its strength in the application of strategies with intangible and non-numeric results, mainly in off-line acting, providing the rise of digital performance and the search for proven results in numbers as a need to apply the methodology. Thus, the general objective of this study is to analyze the introduction of inbound marketing in Brazil, seeking to identify the possible adaptations undergone for the application of the methodology in the national market, besides pointing out the variables of specific objectives as, to describe the points of involvement with the strategic implementation of the inbound marketing methodology in the Brazilian market and analyze the characteristics of the Brazilian market in the search for results and deadlines. The theoretical framework is based on the bibliography of Brian Halligan and Dharmesh Shah, who base their own methodology and report all the bases for the phases of importance within inbound marketing